Autonomous expenditure multipliers and gross value added - Arkadiusz J. Derkacz (Journal of Risk and Financial Management, 2020)
The paper aims to answer two main questions. Is it possible to calculate and analyze fiscal, investment and export multipliers in the short term? The classic approach is mainly based on the input–output balances, which are most often published every 5 years. Is it possible to determine the impact of autonomous expenditure on the growth rate of gross value added? Research and analysis are based primarily on the principle of aggregate demand and the main assumptions of the economic Keynesian model. In the paper, I present theoretical considerations to answer research questions. I have verified the proposed method for calculating the multipliers of autonomous expenditure and the relationship between autonomous expenditure and gross value added in empirical studies. To this end, I have chosen the three economies of the Weimar Group countries. It has emerged that the proposed method allows us to examine the growth rate of value added relative to GDP in the short term, while using the fiscal, investment and export multipliers mechanism.
Keywords: E0; E12; E20; E63; 330; development economy; export multiplier; fiscal multiplier; GVA; investment multiplier; principle of efficient demand